Análisis del impacto de reformas arancelarias 2015-2017 en el sector ensamblador de teléfonos celulares - Gallardo Garces, Katia Rebeca (2018)
Since the end of 2014, the cellular telephone assembly sector has seen the policies implemented by the government affect its commercial and economic situation, all through protectionist measures such as the implementation of safeguards, imposition of a minimum percentage of incorporation of Ecuadorian component and imposition of quotas on the import of cell phones. The objective of this research is to determine the economic and commercial effects caused by the tariff changes of the period 2015 - 2017 in the assembly sector of cell phones, through field research to propose measures to support this sector. This work is an exploratory and descriptive research that makes use of a deductive method and a qualitative and quantitative approach to evaluate the information obtained through the use of research instruments such as the survey and the interview to get to the conclusions of the case study. In this study, it was concluded that imports of both CKD'S and finished cell phones decreased considerably, but not the costs incurred by companies in this sector, ie if there was an affectation for the measures taken by the government in the period of study, both in costs and in sales according to the testimonies of the sector's entrepreneurs.